2015
DOI: 10.1371/journal.pone.0124209
|View full text |Cite|
|
Sign up to set email alerts
|

The Effect of Female Quality on Male Ejaculatory Expenditure and Reproductive Success in a Praying Mantid

Abstract: Strategic ejaculation is a behavioural strategy shown by many animals as a response to sperm competition and/or as a potential mechanism of cryptic male choice. Males invest more mating resources when the risk of sperm competition increases or they invest more in high quality females to maximize their reproductive output. We tested this hypothesis in the false garden mantid Pseudomantis albofimbriata, where females are capable of multiply mating and body condition is an indicator of potential reproductive fitn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…Postmating mate choice (e.g., strategic ejaculate allocation by males, and biased sperm uptake and usage by females) may also be possible, but only a little is known in mantids (Holwell et al. 2010 ; Jayaweera and Barry 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Postmating mate choice (e.g., strategic ejaculate allocation by males, and biased sperm uptake and usage by females) may also be possible, but only a little is known in mantids (Holwell et al. 2010 ; Jayaweera and Barry 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…; Jayaweera et al . ), this is the first empirical evidence of such in a semi‐natural environment. In the current study, we observed multiple matings in more than 50% of trials where females attracted multiple males, and in all other trials, males lingered close to the mating female and oscillated their antennae in her direction until the end of the 2‐day observation period.…”
Section: Discussionmentioning
confidence: 53%
“…If the period of unattractiveness exceeds the time to lay the first egg sac, then polyandry is unlikely and the male is likely to attain 100% paternity within the first egg sac. The time taken by a female to lay her first egg sac depends mainly on female body condition, where good condition females lay 3–4 days after mating (Jayaweera & Barry ), moderate condition females lay 8–9 days after mating (Barry K., unpublished data) and poor condition females lay 10–13 days after mating (Jayaweera & Barry ). In the current study, females laid their first egg sac 13 days after mating, which is longer than the average refractory period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation